Monetary policy can have heterogeneous effects on the investment behavior of women and men - Caterina Forti Grazzini; Chi Hyun Kim (DIW Weekly Report, 2019)
The ultra-loose monetary policy of recent years has raised concerns that the low interest rate environment may overly benefit households with specific demographic and financial characteristics. In this context, monetary policy can be a potential driver of gender wealth inequality, since women are known to be more risk averse, less financially literate, and to participate less in the financial markets than men do. This study focuses on the stock market investment behavior of US households and examines whether monetary policy affects the investment decisions of women and men differently. While monetary policy exclusively affects stock market participation of women, we do not observe any gender difference in the active investment behavior of men and women who invest in stocks. Therefore, increasing stock market participation of women can help prevent the potential distributional effects of monetary policy across gender. Investment plans that would explicitly target female investors could help stabilize and increase stock market participation of women.
Keywords: E58; G11; J16; 330; Gender inequality; Heterogeneous effects of monetary policy; Stock market investment behavior